Chloride-induced corrosion of steel in cracked concrete – Part I: Experimental studies under accelerated and natural marine environments. (January 2016) - Otieno, M.; Beushausen, H.; Alexander, M.
Abstract: Parallel corrosion experiments were carried out for 2¼ years by exposing one half of 210 beam specimens (120 × 130 × 375 mm long) to accelerated laboratory corrosion (cyclic wetting and drying) while the other half underwent natural corrosion in a marine tidal zone. Experimental variables were crack width wcr (0, incipient crack, 0.4, 0.7 mm), cover c (20, 40 mm), binder type (PC, PC/GGBS, PC/FA) and w/b ratio (0.40, 0.55). Results show that corrosion rate ( icorr ) was affected by the experimental variables in the following manner: icorr increased with increase in crack width, and decreased with increase in concrete quality and cover depth. The results also show that the corrosion performance of concretes in the field under natural corrosion cannot be inferred from its performance in the laboratory under accelerated corrosion. Other factors such as corrosion process should be taken into account.